Strategi Pengembangan Potensi Jayengan Kampung Permata Sebagai Kawasan Wisata Budaya di Surakarta - Josephin Fenatama Angel; Rina Kurniati (Jurusan Perencanaan Wilayah dan Kota, 2021)
Kampung Jayengan was formed in the early 19th century, when the royal family asked the jewelers from Martapura to come to Surakarta. Craftsmen were asked to make jewelry for the royal family in collaboration with Chinese ethnic gold entrepreneurs. They settled and married with local residents, so that cultural events took place such as the distribution of ‘Samin’ porridge and